Para além dos “fatos”: o morticínio eleitoral em Cajazeiras - PB (1872-1877) - Silva, Maria Larisse Elias da (2021)
This research was developed along with the Graduate Program in History, with the area of concentration directed to studies on History and Historical Culture, within the research line in History and Regionalities. The object of study was the representations present in the narratives about the electoral killing in Cajazeiras, produced in some newspapers that circulated in the Court, in the Province of Pernambuco and Ceará, in addition to the reports present in the Criminal Proceeding and Annals of the Imperial Senate. The time frame was located between a few years of the seventies of the 19th century (1872-1877), period in which the narratives were propagated by the different regions of the Brazilian Empire. For the development of this research, the theoretical contributions of cultural and social history were fundamental in the process of organizing and questioning the data collected. This study had, for example, contributions based on the concepts of representation, by Roger Chartier, political culture, by Serge Berstein and networks of sociability, by Maria Fernanda Martins and Jean-François Sirinelli – to help build an understanding beyond of the narrated “facts”. To achieve the research objectives, discourse analysis from Micro-History and the perspective of Carlo Ginzburg's evidence and the scale games mechanism proposed by Jacques Revel were used as a methodological tool. The electoral slaughter that occurred on August 18, 1872, served as a backdrop for the propagation of a series of narratives that, in most cases, challenged the electoral system of the Brazilian Empire. However, not only were the narratives organized based on contestations. There were also those who supported the agents of the Court and the counterpoints between the two political notions (of liberals and conservatives) were crossed to better understand the political practices promoted between groups in the brazilian outback, the coast and from the court, to keep himself in power. For all these reasons, this research was dedicated to analyzing four segments that complement each other in the dawn of electoral events in the Empire: the role and influence of family networks in Cajazeiras in the foundation of a local power; an overview of the cases of bloody and fraudulent elections in the Second Kingdom of the Empire of Brazil and how the case in Cajazeiras was inserted into this scenario; the way in which the narratives present in the Judiciary Power unveiled different signs of solidarity networks that were present before, during and after the conflict; and how newspapers created representations around the case that led to the production of a “public opinion” about the ways of doing politics and electoral practices in the second half of the XIX century. Thus, it was possible to understand that there were several interests (political, family, personal and economic) in collision routes when thinking about issues beyond the "facts" and the constructed representations served to qualify the "I" and disqualify the "other", that is, who served or not to be in the Brazilian government.